GEOMETRIC IMAGINATION AS A FACTOR OF THINKING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article focuses on the development of geometric thinking in mathematics lessons in general education schools in the study of geometric objects, the implementation of the relationship between laws and geometry through speech. Aimed at developing students' interest in the subject and the development of their geometric imagination during geometry lessons.